Electric power generation via plate type power generation unit from solar pond using thermoelectric cells. (1st December 2016) - Ding, L.C.; Akbarzadeh, A.; Date, Abhijit
Highlights: The design of a plate type power generation unit coupling with solar pond using TECs is proposed. An open channel power generation unit operates at atmospheric pressure is realised. The power generation unit is able to generate favourable power even at low flow rate. Abstract: Solar pond (SP) has been a reliable supply of heat source for heating process that requires temperature <100 °C. In this work, the capability of solar pond in generating electricity has been explored experimentally using a plate type power generation unit (PTPGU). The open channel PTPGU was designed and fabricated in order to accommodate the TECs. The heat stored in the lower convective zone (LCZ) is used as the heat source needed for generating electricity by utilising thermoelectric cells (TECs) and thus a combined SP-PTPGU system is proposed. The PTPGU was tested with different hot water temperatures and flow rates. Also, the possibility of performance enhancement utilising copper mesh as insertion is presented. From the testing conducted, the PTPGU is able to generate 35.9 W of electricity at the flow rate as low as 5.1 LPM (litre per minute) at the hot water temperature of 81 °C. Besides coupling with solar pond, the PTPGU designed can also be coupled with other type of hot water source, such as hot spring.